2009
DOI: 10.1111/j.1432-2277.2009.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personality and psychological distress on health-related quality of life in kidney transplant recipients

Abstract: Summary Health‐related quality of life (HRQoL) has become an important outcome in the evaluation of kidney transplantation (KT). Although the medical and sociodemographic predictors of HRQoL in patients after KT are well known, there is still a lack of knowledge about the psychological factors involved. This study focuses on the role of personality and actual psychological distress in predicting HRQoL after KT. Sociodemographic (gender, age, education, average income), medical (glomerular filtration, serum alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
6
28
1
5
Order By: Relevance
“…Mayores ingresos económicos y pacientes con renta más alta se correlaciona con mejor percepción de su estado físico y mayor CVRS mental 22,29 . La mayoría de los receptores no observan diferencias en cuanto a los ingresos económicos tras el injerto 89'2%, 9'2% tuvieron ingresos superiores tras la intervención y 1'5% los vieron disminuidos, según un artículo35.…”
Section: Ingresos Económicosunclassified
See 3 more Smart Citations
“…Mayores ingresos económicos y pacientes con renta más alta se correlaciona con mejor percepción de su estado físico y mayor CVRS mental 22,29 . La mayoría de los receptores no observan diferencias en cuanto a los ingresos económicos tras el injerto 89'2%, 9'2% tuvieron ingresos superiores tras la intervención y 1'5% los vieron disminuidos, según un artículo35.…”
Section: Ingresos Económicosunclassified
“…Sin embargo, el neuroticismo solo tiene correlación negativa con la función física (4'4%) y el dolor corporal (4'8%). De manera que cuanto menor sea el neuroticismo y la angustia psicológica mayor CVRS 22 …”
Section: Problemas Psicológicosunclassified
See 2 more Smart Citations
“…CKD represents a serious public health problem worldwide: increasing incidence and prevalence of CKD imposes burden on the utilization of medical care for CKD itself as well as increase in costs of treating complications from CKD [2]. In humans, one of the most sensitive complications, severely decreasing the quality of life, is the cognitive decline [3,4]. Several studies examining the link between the CKD and cognitive outcomes revealed higher rates of dementia and cognitive dysfunction when compared to those in general population [5,6].…”
Section: Introductionmentioning
confidence: 99%